Expanding the ortholog approach for hemophilia treatment complicated by factor VIII inhibitors. (11th November 2014) - Zakas, P. M.; Vanijcharoenkarn, K.; Markovitz, R. C.; Meeks, S. L.; Doering, C. B.
Summary Background The formation of neutralizing antibodies (inhibitors) directed against human coagulation factor VIII (hFVIII) is a life‐threatening pathogenic response that occurs in 20–30% of severe congenital hemophilia A patients and 0.00015% of the remaining population (i.e. acquired hemophilia A). Interspecies amino acid sequence disparity among FVIII orthologs represents a promising strategy to mask FVIII from existing inhibitors while retaining procoagulant function. Evidence for the effectiveness of this approach exists in clinical data obtained for porcine FVIII (pFVIII) products, which have demonstrated efficacy in the setting of congenital and acquired hemophilia. Objectives In the current study, recombinant (r) ovine FVIII (oFVIII) was evaluated for antigenicity and procoagulant activity in the context of human patient‐derived and murine model‐generated FVIII inhibitors. Methods The antigenicity of roFVIII was assessed using (i) inhibitor patient plasma samples, (ii) murine anti‐FVIII MAbs, (iii) immunized murine hemophilia A plasmas and (iv) an in vivo model of acquired hemophilia A. Results Overall, roFVIII demonstrated reduced reactivity to, and inhibition by, anti‐hFVIII immunoglobulin in patient plasmas. Additionally, several hFVIII epitopes were predicted and empirically shown not to exist within roFVIII. In a murine hemophilia A model designed to mimic clinical inhibitor formation, it was demonstrated that inhibitor titers to roFVIII were significantly reduced when compared with the orthologous immunogens, rhFVIII or rpFVIII. Furthermore, in a murine model of acquired hemophilia A, roFVIII administration conferred protection from bleeding following tail transection. Conclusion These data support the investigation of FVIII orthologs as treatment modalities in both the congenital and acquired FVIII inhibitor settings.